Study Of Financial Ratios and Market Performance in Idx High Dividend 20 Companies: Dividend Payout Ratio as An Intervening Variable - Edi Sugiono; Disti Paremono Priatsaleh (International Journal of Management Science and Information Technology, 2025)
This study aims to examine the impact of profitability, liquidity, and leverage on firm value, using the dividend payout ratio as an intervening variable in companies listed in the IDX High Dividend 20 index for the 2021-2023 period. Evaluating a company's performance is crucial for investors when assessing stock growth and overall company value. Profitability, liquidity, and leverage serve as the primary indicators in this research to determine firm value. The study employs a quantitative approach with secondary data obtained from the financial statements of companies listed on the Indonesia Stock Exchange (IDX). The research sample consists of companies included in the IDX High Dividend 20 index for the 2021-2023 period, with complete data on profitability ratio (ROA), liquidity (CR), leverage (DER), dividend payout ratio (DPR), and firm value (PBV). The findings indicate that high profitability enhances firm value by signaling positive prospects to investors, although its effect in this study is not significant. Liquidity has a positive and significant impact on firm value, reflecting that companies with higher liquidity are more trusted by investors due to their ability to meet short-term obligations. Leverage also influences firm value, particularly when companies use debt for profitable expansion. However, excessive debt usage increases the risk of financial distress. Moreover, dividend policy does not affect firm value, suggesting that investors prioritize capital gains over dividends. Profitability does not influence dividend policy, while liquidity shows a negative but insignificant relationship with it. Conversely, leverage affects dividend policy, indicating that higher debt levels have a significant impact on dividend distribution decisions.